Preaxial Polydactyly of the Foot: Variable Expression of Trisomy 13 in a Case from Central Africa - Sébastien Mbuyi-Musanzayi; Aimé Lumaka; Bienvenu Yogolelo Asani; Toni Lubala Kasole; Prosper Lukusa Tshilobo; Prosper Kalenga Muenze; François Tshilombo Katombe; Koenraad Devriendt (Case Reports in Genetics)
Trisomy 13 is a chromosomal disorder characterized by a severe clinical picture of multiple congenital anomalies. We here describe the clinical and genetic features and prognosis observed in a newborn with trisomy 13 from Central Africa. He presented the rare feature of preaxial polydactyly of the feet.